'Index for Inclusion': a framework for school review in the United Arab Emirates. (September 2014) - Alborno, Nadera Emran; Gaad, Eman
<x xml:space="preserve">Abstract</x> This study uses the 'Index for Inclusion', developed by Booth and Ainscow, as a framework for investigating inclusive provision in the United Arab Emirates (UAE), introduced through the 'School for All' initiative. The study, by Nadera Emran Alborno of the American University in Dubai and Eman Gaad of the British University in Dubai, adopts a qualitative research approach, using a multiple case study methodology, to provide a rich and contextualised picture of implementation from the perspective of the various stakeholders. Following the 'Index for Inclusion', the findings are presented in terms of the three key school dimensions of cultures, policies, and practices. Themes emerging from the data include barriers to participation and learning such as the lack of effective training, adequate support services, and inclusive classroom structures. Also included are positive system characteristics such as the welcoming school climate, support among stakeholders, and emerging parent and community involvement. The study provides insights into the possible challenges to the implementation of the 'Index for Inclusion' in schools in the UAE.